TEORI BELAJAR ANDRAGOGI DAN APLIKAINYA DALAM PEMBELAJARAN - Halim Malik (Jurnal Inovasi, 2008)
The theory Andragogi explains how adult learning in study. Adult is interpreted as one who has owned maturity of biological functions, psychological and social in consideration facets, responsibility, and the role of in themeselves life. Andragogi conceived of adult entangling technology in study. Adult learning method is way is organizing participant that they to do learning activity, either in the form of activity of theory and also practice. Study process can happened carefully if method and study technique entangles educative participant. For Young man and adult man, learning is a requirement felt as a compulsion to be fulfilled along the length of age, from the day borned till end of its. Usage of study method in education of implication adult at usage of study technique regarded as compatible is applied in growing behavior of member of learning. The adult learning theory not only to known, but having to can be application in every activity of learning and learns to process or interaction of learning managed by it can take place effectively and efficient.